1989
DOI: 10.1073/pnas.86.17.6724
|View full text |Cite
|
Sign up to set email alerts
|

Surface immunoglobulin-mediated B-cell activation in the absence of detectable elevations in intracellular ionized calcium: a model for T-cell-independent B-cell activation.

Abstract: We recently showed that anti-Immunglobulin conjugated to high molecular weight dextran is 1000-fold more mitogenic for B cells than unconjugated anti-immunoglobulin. This system serves as a model for T-cell-independent ype 2 antigens such as haptenated Ficoll, dextran, and bacterial polysaccharides, which can also stimulate B-cell proliferation and antibody production at low concentrations. We show here that conjugated anti-immunoglobulin, at concentrations that stimulate significant increases in expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
11
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 26 publications
4
11
0
Order By: Relevance
“…Thus, phenotypic and signaling studies indicate that naïve 9G4 B cells express a partially activated phenotype characterized by down-regulation of surface IgM and reduced Ca 2+ flux in response to BCR stimulation similar to mouse anergic B cells [88,89]. This observation would be consistent with the absence of intracellular calcium oscillations observed in B cell activation induced by T cell-independent type 2 antigens [90]. Furthermore, preliminary gene expression experiments using DNA microarrays indicate that as compared to other naïve B cells that regularly participate in productive GC reactions, 9G4 naïve cells express decreased levels of NF-κB and JNK kinase, a profile characteristic of anergic autoreactive transgenic B cells [91,92].…”
Section: Autoreactive 9g4 B Cells Are Censored In a Healthy Immune Sysupporting
confidence: 75%
“…Thus, phenotypic and signaling studies indicate that naïve 9G4 B cells express a partially activated phenotype characterized by down-regulation of surface IgM and reduced Ca 2+ flux in response to BCR stimulation similar to mouse anergic B cells [88,89]. This observation would be consistent with the absence of intracellular calcium oscillations observed in B cell activation induced by T cell-independent type 2 antigens [90]. Furthermore, preliminary gene expression experiments using DNA microarrays indicate that as compared to other naïve B cells that regularly participate in productive GC reactions, 9G4 naïve cells express decreased levels of NF-κB and JNK kinase, a profile characteristic of anergic autoreactive transgenic B cells [91,92].…”
Section: Autoreactive 9g4 B Cells Are Censored In a Healthy Immune Sysupporting
confidence: 75%
“…Moreover, the very recent BCR signaling pathway studies by Reth and his colleagues showed that cre-mediated Syk deletion in Sykflox/Zap-70 mouse primary B cells lowered the phosphorylation of Erk signaling molecule, but not the phosphorylation of Akt-mediated signaling, suggesting that Syk activation and Akt are not necessarily coupled signaling modulus in B-cell activation [41]. The contemporary data in this report echo back the early pioneer studies by Mond and Dintzis and their colleagues showing that anti-Ig (anti-IgM antibody as surrogate antigen) conjugated to dextran will be 1000-fold more potent to drive in vitro B-cell expansion than unconjugated soluble anti-Ig [42], suggesting that stiffness feature of the substrates presenting the antigens would dramatically affect the mutagenicity of these antigens to drive B-cell expansion. Their pioneer studies also distinguished T cell independent type 1 and type 2 antibody responses by immunizing the mice with trinitrophenyl (TNP) conjugated to different types of carriers, including dextran, ficoll, and Brucella Abortus [43,44].…”
supporting
confidence: 69%
“…Thus, phenotypic and signaling studies reveal that while VH4.34 B cells express a partially activated phenotype, they experience a reduced Ca 2+ flux in response to BCR stimulation [46]. This observation would be consistent with the absence of intracellular calcium oscillations observed in B-cell activation induced by T-cell-independent type 2 antigens [47]. Furthermore, preliminary gene expression experiments using DNA microarrays, indicate that as compared to other naïve B cells that regularly participate in productive GC reactions, VH4.34 naïve cells expressed decreased levels of NFκB and JNK kinase, a profile characteristic of anergic autoreactive transgenic B cells [48].…”
Section: Censoring Of Autoreactive Vh434 B Cells In the Healthy Immusupporting
confidence: 73%